Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

transforming quadratic graphs

Transforming Quadratic Graphs class=

Sagot :

Answer:

f(x) = 3(x - 2)² + 4

OR  

f(x) = 3x² - 12x + 16

Step-by-step explanation:

Vertex form of a parabola:

  • y = a(x - h)² + k

Standard form of a parabola:

  • y = ax² + bx + c

Let's find the vertex of this parabola.

  • (h, k) → (2, 4)

In order to find the a-value (vertex form), let's use another point besides the vertex on the parabola.

Using (3, 7) for (x, y), let's substitute this point and the vertex (2, 4) for (h, k) into the vertex form equation and solve for a.

  • 7 = a[(3) - (2)]² + 4

Simplify using PEMDAS.

  • 7 = a(1)² + 4
  • 7 = a + 4

Subtract 4 from both sides.

  • a = 3

Now we have (h, k) and a of the vertex form.

  • y = a(x - h)² + k  → y = 3(x - 2)² + 4

In order to convert from vertex to standard form, simplify the equation by FOILing.

  • y = 3(x - 2)² + 4
  • y = 3(x² - 4x + 4) + 4

Distribute 3 inside the parentheses.

  • y = 3x² - 12x + 12 + 4

Combine like terms.

  • y = 3x² - 12x + 16

Therefore, we have the answer:

Vertex form:

  • f(x) = 3(x - 2)² + 4

Standard form:

  • f(x) = 3x² - 12x + 16